Conferences on nonlinear problems of mathematical physics and problems with free boundaries - Bazaly , В. V.; Skrypnik , I. V.; Tedeev , A. F.; Базалий , Б. В.; Скрыпник , И. В.; Тедеев , А. Ф. (Institute of Mathematics, NAS of Ukraine, 1992)
-